Peningkatan Literasi Keuangan Melalui Peran Galeri Edukasi Investasi Sebagai Media Pembelajaran Pasar Modal Interaktif Siswa/I SMAN 18 Batam - Tiara, Tiara; Aprayuda, Riyadi; Kholisa Dinuka, Vina; Wahana Warga Dalam, Winanda; Alif Dzulfiqar, Mohamad; Marcelina Soraya, Iassa; Zainuddin, Muhammad (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to provide an overview of increasing understanding of financial literacy and student responses through interactive learning media in the Investment Education Gallery. This research data was collected from 47 participants who participated in structured activities consisting of a pre-test and post-test in the form of true and false questions, then confirmatory questions related to student responses related to the role of the Investment Education Gallery as an interactive learning medium. This research found differences in scores between the pre-test and post-test. The t-test paired samples test shows that the results have significant differences descriptively. The post-test results are higher than the pre-test, meaning that after participating in socialization and mentoring activities in a series of investment education gallery activities, students' understanding has increased; apart from that, students/gave a positive response when following the learning progress as seen from being on a scale of 4, namely strongly agree and know. This research contributes to providing evidence that the role of the Investment Education Gallery in schools can be used as a teaching medium that can directly increase financial literacy, now felt by students at school.